Efek kualitas layanan pada loyalitas pelanggan: peran mediasi kepuasan pelanggan - Ani Sugiarti Ningsih; Iva Nurdiana Nurfarida (MBR (Management and Business Review), 2022)
The aim of the study was to investigate the effect of service quality on customer loyalty in Food and Beverages during the Covid-19 pandemic, and to examine the mediating role of customer satisfaction. This research is a survey research with a quantitative approach, conducted on 110 people of Food and Beverage MaxOne Ascent Hotel Malang customers using the accidental sampling method. Data were collected using a questionnaire and analyzed by Path Analysis. Using a quantitative research approach with a survey method, it was carried out on 110 people of Food and Beverage MaxOne Ascent Hotel Malang customers using the accidental sampling method. Data were collected using a questionnaire and analyzed by Path Analysis. The results of this study indicate the positive effect of service quality to increase customer loyalty, service quality will also increase customer satisfaction, and its impact on customer loyalty. Quality service is an important factor to create customer satisfaction and ultimately encouraging the realization of customer loyalty. Future research needs to consider experiential marketing as a determinant of customer satisfaction with services